Canadian perspectives of digital mental health supports: Findings from a national survey conducted during the COVID-19 pandemic. (May 2022) - Shen, Nelson; Kassam, Iman; Chen, Sheng; Ma, Clement; Wang, Wei; Boparai, Navi; Jankowicz, Damian; Strudwick, Gillian
Objectives: The impact of the COVID-19 pandemic on population mental health has highlighted the potential for digital mental health to support the needs of those requiring care. This study sought to understand the digital mental health experiences and priorities of Canadians affected by mental health conditions (i.e. seekers, patients, and care partners). Methods: A national cross-sectional electronic survey of Canadians was administered through a market research firm's survey panel. Seekers, patients, and care partners were asked about their digital mental health experiences (e.g. uptake, barriers to access) and priorities. Survey responses were summarized using descriptive statistics. Results: Overall, 1003 participants completed the survey. 70.2% of participants routinely use digital mental health supports to support themselves or those they care for; however, only 28.6% of participants are satisfied with the available digital mental health supports. Most participants (73.3%) have encountered some barriers when accessing digital mental health supports. Awareness of digital mental health supports was a top barrier identified by participants. The top digital mental health priorities consisted of digital mental health curation, navigation, and a digital mental health passport. Conclusions: Most participants use digital mental health supports for themselves or others, however, many are unaware of digital mental health supports available. Efforts to improve navigating access to digital and in-person mental health services are seen as a top priority, highlighting the need to enable seekers, patients, and care partners to find the appropriate support and make decisions on how to best improve their mental health.